Sustaining Gnetum L. (Gnetaceae) in Africa through improved taxonomy and domestication - Biye, Elvire Hortense (My University, 2014)
Gnetum L. (Gnetales) plants are useful gymnosperms in Africa that alleviate poverty in the local community as they are widely sold and used as vegetable (‘eru’). The African species of this genus are however difficult to distinguish from one another, are threatened due to over-exploitation and therefore face the risk of disappearing before they are adequately known. This study aims to clarify the taxonomy of the vulnerable Gnetum species in Africa and to promote sustainable utilization and conservation of the species. Thus, sustainable strategies involve, on the one hand, the identification of various species suitable for conservation and, on the other hand, the supply of management guidelines for cultivation based on taste data. The specific objectives undertaken in the genus Gnetum in Africa are to: - investigate the various species to be recognized in the genus in Africa and the important features that distinguish them. - determine how the cultivated material relates to the naturally occurring taxa. - elucidate species limits based on genetic patterns. - identify anatomical features useful to distinguish species in general and to match female plants to corresponding males in particular. - evaluate any variation in taste between Gnetum populations. - examine the mechanism involved in seed germination in order to promote their sustainable utilization in cultivation. To address the taxonomic problems in the genus Gnetum in Africa, the types and the original descriptions were used to identify and help attribute names to the various forms; numerical analyses of morphological characters were carried out to illustrate the distribution of any variation among various specimens; molecular and anatomical tools were also used to reveal additional characters to differentiate and recognize species and to match male and female specimens. In an attempt to sustain Gnetum plants in Africa so that the lives of those who depend on it are not affected in the near future, several strategies are undertaken. Taste analysis was applied to explore species with the best taste for promotion and the type of leaves to harvest thus limiting mass destruction of the entire Gnetum plant. So variation in taste of the leaves of Gnetum (‘eru’ meal) with respect to species, provenance and age of leaf was investigated using both questionnaire survey and the gustatory approach. Seed germination trials were carried out as a possible means to selective cultivation that could result in the bulk production of Gnetum plants and so relieve pressure on natural populations. Gnetum species in Africa present different morphological structures useful for taxonomic clarification. These species are better distinguished morphologically by their reproductive structures; the vegetative features vary within species and even on the same specimen. The original applications of the names Gnetum africanum Welw. and Gnetum buchholzianum Engl. have been clarified and two new African species have been identified: Gnetum interruptum E.H. Biye sp. nov. and Gnetum latispicum E.H. Biye sp. nov. A key to these species is provided and useful characters to recognize species in the genus Gnetum in Africa are discussed. Taste analysis permitted the identification of specific factors for horticulturalists to know which species to propagate for leaves of Gnetum. For example in the course of the investigation, it was found that the leaves of G. buchholzianum taste best in ‘eru’ meals, that good Gnetum leaves for ‘eru’ were collected from every region but only the young leaves were best for ‘eru’ meals. In addition, seeds of Gnetum species in Africa are orthodox i.e. they exhibit dormancy but nevertheless they germinate under artificial or nursery conditions when exposed to the appropriate treatments. The study clarified the taxonomic status of Gnetum species in Africa and also provided information to identify the forms with good agronomic traits and the conservation strategy to explore in order to sustain Gnetum in Africa for future uses.
Keywords: Gnetaceae.